3-T in-bore MR-guided prostate biopsy based on a scoring system for target lesions characterization. (December 2013) - Quentin, Michael; Schimmöller, Lars; Arsov, Christian; Rabenalt, Robert; Antoch, Gerald; Albers, Peter; Blondin, Dirk
Background: To estimate potential malignant lesions within the prostate gland, the usage of a scoring system has recently been proposed by a European consensus meeting. Purpose: To prospectively investigate a scoring system for functional prostate magnetic resonance imaging (MRI) using in-bore MR-guided prostate biopsy at 3-T. Material and Methods: Prostate MRI examinations of 59 patients (between February 2011 and May 2012) with no known prostate cancer, elevated prostate specific antigen (PSA) level, and unsuspicious digital rectal examination were included in the study. In each patient up to three lesions were defined and scored using a 5-point scoring system for each MR sequence (T2-weighted images, diffusion-weighted imaging, dynamic contrast-enhanced imaging). Following MRI-guided in-bore biopsy these lesions were correlated to the histopathological findings. Results: A total number of 144 lesions were defined in 59 patients. In 28 patients (51 lesions) MR-guided in-bore biopsy was positive for tumor (Gleason grade 6 or higher). A cut-off limit of 10 or more points in summation of the individual scores of all three sequences was used, leading to a 90% sensitivity, 63% specificity, 58% positive predictive value, and 92% negative predictive value. Conclusion: A simple 5-point scoring system of functional prostate MRI achieves excellent sensitivity and moderate specificity for directing 3-T-guided prostate biopsy relative to the histopathological findings.